(untitled) (Third Sector Social Economic Review, 2023)
The seasonality phenomenon, which is frequently examined in the inflation series, has not been found in the literature on the interest rate determined by the financial sector and related to inflation. The findings of the study show that there is seasonality in level and volatility in the period 2001:01-2023:05 in the eight interest rate variables examined for Turkey. Similar findings are obtained in the alternative specification of seasonality in volatility.